Factors influencing entrepreneurial behaviour of farm women involved in vegetable farming: An empirical analysis - YADAV, D S; CHAHAL, V P; SINGH, UMMED; KUMAR, ARVIND; SOOD, PANKAJ; THAKUR, S K (The Indian Journal of Agricultural Sciences, 2014)
The study was conducted with the objective to identify the factors influencing the entrepreneurial behaviour of farm women in vegetable enterprise in Mandi district of Himachal Pradesh, India. The data collected from 100 farm women of two blocks of the district by personal interview using multi-stage sampling technique revealed that majority of respondents had low to medium level of management orientation, economic motivation, risk orientation, self confidence, moderate to high level of achievement motivation and leadership ability. The majority respondents had low level of utilisation of available assistance, medium level of farm decision making, less innovative and poor level of knowledge about the enterprise. The overall entrepreneurial behaviour of majority respondents (92%) was of low to medium level. Except age and family size, all the personal attributes of the respondents were positively and significantly correlated with overall entrepreneurial behaviour. The regression coefficient of formal education, experience in enterprise, information sources utilization and scientific orientation were significant emphasizing the need to concentrate more on these factors for promoting entrepreneurship development among the vegetable women farmers. Apart, these farm women should be encouraged for formation of groups and made aware of technical knowhow through trainings, demonstrations and exposure visits besides strengthening the marketing facilities in the area. The co-efficient of determination (R2) explained 47.35 per cent of variation in the entrepreneurial behaviour by all the variables together emphasizing the need of identification of other unidentified variables through future research.